SCR 2019
DOI: 10.35715/scr1002.113
|View full text |Cite
|
Sign up to set email alerts
|

The Right to a Nationality and the Right to Adequate Housing An Analysis of the Intersection of Two Largely ‘Invisible’ Human Rights Violations

Abstract: Millions of individuals around the world face challenges enjoying their right to a nationality, and millions more face challenges enjoying their right to adequate housing. While these human rights violations are recognised in general terms, little research has considered the extent to which these human rights abuses intersect as stateless persons face violations of specific socioeconomic rights, especially the right to adequate housing. This research attempts to fill that gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These living conditions harm children's human dignity (Leary, 1995;Bueren, van, 1998;UN crc General Comment No. 21, 2017;Sandbergen, 2018;Gronowski, 2019). Research has found that living in deplorable housing conditions makes children even more vulnerable than adults living in the same situation, given the negative impact it has on their development (UN Special Rapporteur on housing, 1995;Eide, 2006;Nolan, 2011;Malone, 2015;Wilkinson, 2017;Lansdown, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These living conditions harm children's human dignity (Leary, 1995;Bueren, van, 1998;UN crc General Comment No. 21, 2017;Sandbergen, 2018;Gronowski, 2019). Research has found that living in deplorable housing conditions makes children even more vulnerable than adults living in the same situation, given the negative impact it has on their development (UN Special Rapporteur on housing, 1995;Eide, 2006;Nolan, 2011;Malone, 2015;Wilkinson, 2017;Lansdown, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the crc Committee and research literature, these children's right to adequate housing is under severe pressure (UN crc gc No. 21, 2017;Sandbergen, 2018;Gronowski, 2019). A growing body of research shows that the failure to prevent homelessness and living in substandard housing results in violations of the right to adequate housing, as laid down in, inter alia, Art.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations